Perfil bioquímico sérico de galinhas poedeiras na região de Araçatuba, SP - De Sousa Barbosa, Tatiana [UNESP]; Mori, Carolina Kimie [UNESP]; Polônio, Lorrayne Bernegossi [UNESP]; Ponsano, Elisa Helena Giglio [UNESP]; Ciarlini, Paulo César [UNESP] (Universidade Estadual de Londrina, 2011)
The establishment of reference values is extremely important for successful diagnosis and treatament. Considering that in most species the serum chemistry profile is influenced by race, climate and management, we decided to determine the values of aspartate aminotransferase (AST), alanine aminotransferase (ALT), uric acid, creatinine, creatine kinase (CK), phosphatase alkaline (ALP), gamma-glutamyltransferase (GGT), total protein (TP) and albumin of Dekalb hens in the region of Araçatuba - SP. All samples were processed soon after harvesting in an automatic biochemical analyzer calibrated and monitored with control serum levels I and II. The following confidence intervals were obtained: 44-65,5 U / L (AST); 18,4-21,2 U / L (ALT), 2.1-2.5 mg / dL (uric acid); 1.7 to 5.7 U / L (CK); CI 1.2-2.2 mg / dL (creatinine), 1276-1506 U / L (FA); 18-23,4 U / L (GGT); 27.12 to 29 g / L (PT), from 11.4 to 12.16 g / L (albumin).
Serum biochemical profile of laying hens in the region of Araçatuba, SP
Keywords: Analysis; Biochemical profile; Poultry; Reference values